Contrast-Enhanced Dynamic MR Imaging of Uterine Fibroids as a Potential Predictor of Patient Eligibility for MR Guided Focused Ultrasound (MRgFUS) Treatment for Symptomatic Uterine Fibroids. (25th July 2010) - Yoon, Sang-Wook; Lee, Chan; Kim, Kyoung Ah; Kim, Sang Heum
Abstract : Magnetic resonance-guided focused ultrasound surgery (MRgFUS) is a non-invasive treatment approach for symptomatic uterine fibroids. One imaging characteristic considered in selecting patients who may benefit from MRgFUS of their uterine fibroids is the signal intensity of the fibroid compared with surrounding myometrium on T2-weighted MR images. Previous reports suggest that hyper-intense fibroids are less amenable to MRgFUS compared with iso- or hypo-intense fibroids. In this case study, we utilized contrast-enhanced dynamic MR imaging to further characterize the vascularity of a hyper-intense fibroid. Based on the results of dynamic T1-weighted contrast-enhanced images, we assumed that the hyper-intense appearance resulted from high fluid content rather than high vascularity and predicted that the fibroid would respond to MRgFUS. The patient underwent the MRgFUS without complication and reported significant decrease in fibroid symptoms at 3 and 12 months post-treatment. This case suggests that pre-treatment dynamic contrast-enhanced imaging used in conjunction with T2-weighted imaging may improve the criteria for selecting uterine fibroids amenable to treatment with MRgFUS, potentially leading to improved patient outcomes.